Crime and the Chinese Dream - Bakken, Borge (Book collections on Project MUSE., 2018)
Although official propaganda emphasizes the Chinese Dream as the dream of all Chinese, the opportunities of achieving prosperity by legal means are distributed unequally. Crime and the Chinese Dream reveals how people on the margins of Chinese society find their way to the Chinese Dream through illegal or deviant behaviors. The case studies in this book include corrupt doctors in public hospitals in Beijing, fraudsters in a village called "cake uncles," illegal motorcycle taxi drivers in Guangzhou, drug users being "reeducated" in detention centers, and internet addicts who are treated as criminals by the system. Despite the patriotic and collectivistic tint of the official dream metaphor, the contributors to this volume show that the Chinese Dream is essentially a state capitalist dream, which is embedded within the problems and opportunities of capitalism, as well as a dream of control.